THE EFFECTIVENESS OF THE APPLICATION OF SCIENTIFIC LITERACY-BASED NATURAL SCIENCE TEACHING SET TOWARD THE STUDENTSâ LEARNING ACTIVITIES AND OUTCOMES ON THE TOPIC OF THE INTERACTION OF LIVING ORGANISM AND ENVIRONMENT - Widiyanti, F.; Indriyanti, D. R.; Ngabekti, S. (Jurnal Pendidikan IPA Indonesia, 2015)
This research was aimed to find out effectiveness of the application of scientific literacy-based natural science teaching set toward the studentsâ learning activities and outcomes on the topic of The Interaction of Living Organism and Environment. This study is a quasi-experimental study of non-equivalent type (pretest-posttest). The results showed that the teaching set was effective, as proved by the t-test of the learning outcomes of the experimental group (t4,78> t1,66) which was different to the control group (thitung>t1,66), the results of the experiment group n gain average was 0,55 and the control group was 0,39 which was in the average category. The t-test value of the activities in the experimental group (t3,52>t1,66) was different to the control group (thitung>t1,66). Based on the analysis results, it could be concluded that the application of the scientific literacy-based natural science teaching set was effective toward the studentsâ learning activities and outcomes.